The Effect of Fermentation Time on The Organoleptic Test of Kombucha Tea - M. Ali Akbar; Khairunnisa Khairunnisa; Mardiah Mardiah; Ekariana S Pandia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Kombucha is a fermented product of sweet tea solution which is added with kombucha starter and scoby. Kombucha culture is a combination of bacteria and yeast called SCOBY (Symbiotic Culture of Bacteria and Yeast). This activity aims to determine the effect of time on the organoleptic test in making kombucha tea. This study used quantitative methods and data collection techniques by conducting organoleptic tests on respondents, in this study using a completely randomized design (CRD). Organoleptic consisting of taste, aroma and color. The results showed that on average all respondents preferred kombucha tea on the 15th day of fermentation. The organoleptic test conducted on 30 respondents had a preference level with the highest percentage for each parameter consisting of 60% taste, 70% aroma and 70% color. Where the longer the fermentation time, the level of preference of the testers for the organoleptic response increases.